Respuesta :
Answer:
Step-by-step explanation:
RS + ST = RT
6y + 3 + 4y + 7 = 60
6y + 4y + 3 + 7 = 60
10y + 10 = 60
10y = 60 - 10
10y = 50
y = 50/10
y = 5
RS = 6*5 + 3 = 30 +3 = 33
ST = 4*5 + 7 = 20 + 7 = 27
Step-by-step explanation:
[Diagram in image attached]
RS + ST = RT
(6y +3) + (4y + 7) = 60
6y + 3 + 4y + 7 = 60
10y + 10 = 60
10y = 60 - 10
10y = 50
y = 50/10
y = 5
RS = 6y +3 = 6(5) + 3 = 30 + 3 = 33
ST = 4y +7 = 4(5) + 7 = 20 + 7 = 27
RT = 60
{RS + ST = RT
33 + 27 = 60}
HOPE THIS HELPS YOU
MARK AS BRAINLIEST
![Ver imagen ruhaan22](https://us-static.z-dn.net/files/df8/913ffc0f79f16816491055ca34eeb6b2.jpg)